The impact of COVID-19 on music venues in regional South Australia: A case study. Issue Volume 21:Number 1(2021)Special Issue:Part 1 (28th August 2021) - Roberts, Rosie; Whiting, Sam
Abstract : As spaces of social, cultural and economic production, small regional music venues are an under-explored research area that can offer insights into changing music and performance practices, place-making, and the connections between urban and regional communities. Within the context of the COVID-19 crisis, the state of precarity in which such venues operate is emphasized and exacerbated. This article will present preliminary findings from our case study of a small, regional music venue in the mid-north of South Australia that has been heavily affected by the COVID-19 pandemic and associated government restrictions. The pandemic has dramatically changed the way that live music is both performed and experienced, and a case study such as this offers an opportunity to discuss its impact on niche cultural and community spaces that are geographically and socially removed from the urban milieu and its policy settings. Preliminary findings suggest COVID-19 brought about both challenges (capacity restrictions and disruption of interstate travel for audiences and artists) as well as opportunities (strengthening the presence of rural voices in policy settings). The case study also highlights the need for further research on strategies for developing and sustaining regional touring pathways throughout South Australia.